A study in turning of AISI D2 steel with textured and non-textured coated carbide tool at the flank face. (2020) - Sarma, Deba Kumar; Rajbongshi, Sanjib Kr
Abstract: Surface texturing of a cutting tool is a new technique which can enhance the cutting performance during machining. In the present work micro-EDM is applied to produce texture at the tool flank face. Two types of texture, i.e. groove and dot are made at the flank face of a coated carbide tool for machining AISI D2 steel. For comparison purpose, machining is performed using non-textured tool also. Cutting speed, feed and depth of cut are selected as the cutting parameters, each having two levels. The cutting force and feed force are considered as main performance parameters beside surface roughness and flank wear. From the experimental study, it is noticed that textured tool gives low values of cutting and feed forces during machining as compared to a non-textured tool. In comparison to groove-texturing tool, dot-texturing tool generates less cutting and feed forces. Both the texturing tool gives fine surface finish and less flank wears in comparison to non-textured tool.